The Effectiveness of Imposing Sanctions on Notaries/PPAT Recipients of Work Given by Pt. Regional Development Bank of West Java and Banten Tbk,. Consequences of Work that Exceeds the Completion Period/Service Level Agreement (SLA) - Sugiarti, Stephanie (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The work of a Notary/PPAT as a bank partner often experiences obstacles in the process, so that the obstacles that arise result in the work of the Notary/PPAT being completed beyond the completion period/Service Level Agreement (SLA), as stated in the Cooperation Agreement between the Notary/PPAT and bank. This study aims to determine the level of effectiveness of imposing sanctions on Notaries/PPAT Bank partnersas a result of work that has passed its completion period, along with obstacles and solutions to reduce the non-fulfillment of Notary/PPAT Partner obligations to banks. The research approach method used in this thesis isnamely the sociological juridical approach. The specification of the research used is analytical descriptive. The type of data used in this research is primary data which includes the applicable laws and regulations in Indonesia. The results of the study show that: First, 91% of the 33 (thirty three) Notaries/PPAT partners at the Regional Office III of bank BJB are of the opinion that the imposition of sanctions is very effective as a preventive measure for the bank against the large number of Notary/PPAT work that has not been completed and exceeds the SLA. Second, for work that goes beyond the SLA, as much as 9% is hampered by binding credit, both credit agreements and addendums, while as much as 91% of work is hampered by binding collateral, such as Mortgage, Fiduciary, Mortgage, and Pledge. The solution to this problem is to evaluate the performance of the partner Notary/PPAT, regular monitoring, and reconciliation.Keywords: Agreement; Cooperation; Effectiveness; Sanctions.Â